Knowledge, Awareness, Perception and Attitude Regarding Anti-USAG-1 Gene Therapy for Tooth Regeneration - Nivas, Dr. Ch.; Pratap, Dr. K. V. N. R.; Padma, Dr. T. Madhavi; Kumar, Dr. Srujan; Singh, Dr. Surbhit; Prasanna, Dr. V. (International Journal Of Drug Research And Dental Science, 2025)
Background: Tooth loss remains a major global oral health issue affecting function, aesthetics, and quality of life. Current tooth replacement options, such as implants and dentures, have limitations related to biological integration and cost. Recent advances in regenerative dentistry have identified the anti- USAG-1 (Uterine Sensitization-Associated Gene-1) gene therapy as a promising approach to stimulate natural tooth regeneration.Understanding dental students’ knowledge, awareness, perception, and attitude toward this emerging field is essential for integrating regenerative technologies into future clinical practice.Objective: To assess the knowledge, awareness, perception, and attitude regarding anti-USAG-1 gene therapy for tooth regeneration among undergraduate dental students.Methods: A cross-sectional questionnaire-based study was conducted among undergraduate dental students. The survey evaluated four domains: knowledge of anti-USAG-1 gene therapy, awareness of its applications in tooth regeneration, perception of its benefits and ethical implications, and attitude toward incorporating gene-based therapies in dentistry.Results: Most participants demonstrated limited knowledge and awareness of anti-USAG-1 gene therapy, reflecting the novelty of the topic. However, the majority showed a positive attitude and interest in learning about gene therapy as a future treatment modality. Students perceived gene therapy as a potential revolution in regenerative dentistry, though they expressed concerns about cost, ethical considerations, and lack of clinical exposure.Conclusion: Undergraduate dental students exhibited low knowledge but positive attitudes toward anti-USAG-1 gene therapy for tooth regeneration. Strengthening genetic and molecular biology components within the dental curriculum and conducting workshops or seminars on regenerative biotechnology can enhance preparedness for future clinical integration.